E-government as a communication tool in the construction process - Błażewski, Maciej (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
E-government increases the efficiency and quality of service of public administration. The development of e-government covers only some aspects of the construction process, including: registers; electronic patterns of documents; transfer of documents to other authorities; activities in administrative proceedings. E-government is conducted inside public administration and between the authorities and citizens. E-government in the construction process is governed by, inter alia: the Act of Construction Law, the Act on promulgation of normative acts and certain other legal acts; the Code of Administrative Proceedings.
Keywords: construction process; register; electronic communication; administrative proceeding; E-government